Analisis Pemikiran Abu Yusuf Tentang Sistemik Praktis Pembebanan Pajak Berdasarkan Kemampuan Membayar (Ability To Pay) - unang Fauzi Bajuri; Muhammad Naufal Hilmi (INSTITUT AGAMA ISLAM TAZKIA, 2019)
Unang Fauzi , * Muhammad Naufal Hilmi Abstract. This thesis based on the background of the problem is the system of taxation with the ability to pay ( ability to pay) in the mind of Abu yusuf. Abu Yusuf was one of the most successful scientists and thinkers of the period of the caliph Harun Ar-Rashid, as seen from the progress of the country and the welfare of its people. During the caliphate of Harun Ar-Rashid, Abu Yusuf's book entitled al-kharaj, became a guide for the economic system in the period of the caliph Harun Ar-Rashid, especially in the field of taxation, so Abu Yusuf replaced the system during the caliphate of Harun Ar-Rashid, namely ( wazifah) system collected with a fixed value to be a system muqasamah (proportional system) system collected with consideration of ability level and percentage of income. Abu Yusuf preferred the proportional tax collection system (muqasamah) applied to the United Nations (Land and Building Tax) and VAT (Value Added Tax), whose definition is definition of proportional tax synonymous(muqasamah) with the with the system of ability to pay (Ability To Pay)/ progressive rates applied to PPh (Income Tax), compared to the fixed tax system (separate). In setting up a tax collection system, there needs to be benefits for the people. This study aims to find out how Abu Yusuf views the tax burden system, especially on the ability to pay system (ability to pay) whether it provides mashlahah if applied in Indonesia ?. The data collection technique used is the library research technique (Library Research). The results of this study show that with the imposition of taxes based on the system of ability to pay in the collection of taxes can provide mashlahah according to Abu Yusuf, although there are some who oppose the implementation. The benefits that Abu Yusuf meant were done by keeping personal interests (the apparatus, government, and rulers) and prioritizing the interests of society.